Emission-line oscillations in the dwarf nova V2051 Ophiuchi - Steeghs, D; O'Brien, K; Horne, K; Gomer, R; Oke, J (2001)
We have detected coherent oscillations, at multiple frequencies, in the line and continuum emission of the eclipsing dwarf nova V2051 Ophiuchi using the 10-m Keck II telescope. Our own novel data acquisition system allowed us to obtain very fast spectroscopy using a continuous readout of the CCD on the LRIS spectrograph. This is the first time that dwarf nova oscillations have been detected and resolved in the emission lines. The accretion disc is highly asymmetric with a stronger contribution from the blueshifted side of the disc during our observations. The disc extends from close to the white dwarf out to the outer regions of the primary Roche lobe. Continuum oscillations at 56.12s and its first harmonic at 28.06s are most likely to originate on the surface of a spinning white dwarf with the fundamental period corresponding to the spin period. Balmer and helium emission lines oscillate with a period of 29.77s at a mean amplitude of 1.9 per cent. The line kinematics and the eclipse constraints indicate an origin in the accretion disc at a radius of 12 ± 2Rwd. The amplitude of the emission-line oscillation modulates (0-4 per cent) at a period of 488s, corresponding to the Kepler period at R = 12Rwd. This modulation is caused by the beating between the white dwarf spin and the orbital motion in the disc. The observed emission-line oscillations cannot be explained by a truncated disc as in the intermediate polars. The observations suggest a non-axisymmetric bulge in the disc, orbiting at 12Rwd, is required. The close correspondence between the location of the oscillations and the circularization radius of the system suggests that stream overflow effects may be of relevance.